PEDAGOGUE-CATHOLICOS KAREKIN I’S APPROACHES AND VIEWS ON THE TEACHER’S VOCATION AND MISSION (EDUCATION IN THE 21ST CENTURY, 2025)
The role and significance of the teacher in organizing the educational process have been indisputable, and this remains relevant today. In light of dynamic societal changes, there is a growing need to reconsider and reshape the image of the teacher—developing professionals endowed with high personal and professional qualities. No educational technology can support a teacher in effectively fulfilling their professional duties if the teacher is not personally and professionally prepared.It is no coincidence that in all historical periods, the figure and profession of the teacher have been highly valued. Today, in the era of emerging technologies and artificial intelligence, the teacher’s role is even more vital—as a moral guide, a carrier and transmitter of values, a researcher, and an innovator capable of responding to the challenges of the 21st century.A striking embodiment of an inspiring educator and innovative researcher is His Holiness Karekin I, Catholicos of All Armenians, who remained true to the values he instilled in his students throughout his prolific pedagogical career. Dedicating the greater part of his rich and meaningful life to the grateful and selfless mission of a pedagogue and mentor, the Supreme Patriarch defined the essence of a true educator and teacher, grounding it in the fundamental components of self-development and devotion.
Keywords: education; upbringing; innovative teacher; researcher-pedagogue; personal qualities of the teacher; professional competencies